Information Communication Technology and Service Delivery in Nyagatare District Local Goverment, Rwanda. - Wellars, Kanamugire (Kabale University, 2020)
The study analyzed how Information Communication Technology was influencing survive delivery in Nyagatare District Local Government.it was guided by four objectives, namely to analyze the various ICT facilities available and used by Nyagatare District Local Government, to investigate the role ICT has played in improving service delivery in Nyagatare district local Government; to analyze the challenges hindering the implementation of ICT and service delivery in Nyagatare district Local Government; and to investigate intervention measures for addressing the challenges hindering the implementation of ICT and service delivery in Nyagatare local Government The Literature review for the study was extracted from different textbooks, manuals, reports, journals and websites from different libraries and computer laboratories. The entire research process involved proposal writing, data collection, data analysis, presentation and discussion of results. The study was both qualitative and quantitative in nature. Both simple random and purposive sampling techniques were used to select one hundred and twenty (120) respondents for study. The researcher used the Questionnaire, observation and interview guides to collect primary data from the field. Data was presented in tables, figures and plates. Conclusion and recommendations of the study were drawn basing on the result of the study. The study findings revealed that the majority of respondents (27) noted that there were office intercom/mobile phones to ease communication and influence better service delivery in the study area. The study findings also recorded that the majority of respondents (98%) were aware of the various ICT facilities that were available and used by Nyagatare district Local government. The study further indicated that the majority of respondents (94%) noted that ICT had played any role in improving service delivery in the study area. Among the role ICT had played in improving service delivery in the study area included quick service delivery and quick retrieval of information whether it was needed for use. However, the study findings concluded that the majority of respondents (90%) noted that there were challenges that hindered the implementation of ICT and service delivery in the study area. Among the challenges included inadequate ICT facilities in the study area and ineffient top-down provision of information. Among the sustaining factors for persistence of the challenges included budget constraints and corruption. The study also concluded that majority the majority of respondents (94%) were aware of the measures in place that addressed the challenges that were hindering the implementation of ICT and service delivery in the study area. The study further concluded that Nyagatare District Local Government should fundraise for ICT donations in terms of training facilitation fees, CT equipment such as computers, to help the members of staff, administration and other stake holders to acquire the necessary skills and equipment for better service delivery in the study area and that there should be favorable government policy that boosts the moral of the private and public investors into ICT business so that there is visible ICT operations in the study area for effective service delivery among other suggested intervention mechanisms to boost ICT for effective service delivery. Basing on the study findings, the study recommends that in the wake of increasing challenges to deliver quality of public services in district local governments in developing counties like Rwanda, it is better to encourage ICT in all development projects of local governments and make the citizens happier with timely and cost savings in availing services and improvement in the reliability of services. The study further recommends that special emphasis is needed in working out revenue models, ensuring the full implementations of ICT through appropriate tenure appointment of project champions, ensuring effective monitoring and maintenance of ICT systems, among others.